Inducing environmental co-operation by the design of emission permits - Cornelia Ohl (Fondazione Eni Enrico Mattei (FEEM), 2002)
Strategies of international risk management, as the implementation of tradable emission permits, feed back to the incentive structure of a treaty, like the Kyoto Protocol. Discussing the Kyoto Protocol the question was: Should there be any restrictions on the trading of emission permits or not? With the help of a simple two country model it is shown that the enforcement of environmental treaties critically depends on the type and the intensity of national risk preferences. Assuming that the 'global alliance of risk' decreases with each co-operative contribution, risk aversion is a prerequisite for enhancing the chances of global risk management. It is moreover the national intensity of risk aversion that determines whether trade should be restricted or not. In some cases the chances of international coalition formation are expected to improve only if less risk averse countries dictate the rules of the game, here: the design of the permit regime.
Keywords: D7; D8; F1; H4; Q2; 330; Environmental co-operation; country-specific risk preferences; game theoretic approach; typology of co-operative behaviour; design of emission permits; Emissionshandel; Umweltabkommen; Klimaschutz; Internationale Zusammenarbeit; Risikopräferenz; Spieltheorie; Theorie